Low impact vehicle battery supply chains: assessing the impacts of alternative procurement strategies. (21st September 2021) - Rafele, Carlo; Gallo, Claudio; Mangano, Giulio; Cagliano, Anna Corinna; Carlin, Antonio
This work aims at supporting decision-making related to make or buy strategies for procuring batteries assembled on electric and hybrid vehicles for a car manufacturer that is introducing new models in its portfolio. In particular, several supply chain scenarios have been defined according to the battery architecture. The results show that the purchase of complete batteries implies the highest costs and CO2 emissions. On the contrary, buying single components helps improving these aspects, but it requires a certain level of vertical integration by the car manufacturer together with specific know how. Finally, purchasing modules results in the lowest costs due to a reduced number of trips due to the product structure. Thus, this paper proposes a framework to guide automotive companies in effectively designing make or buy strategies in their battery supply chain by comparing alternative vertical integration levels.